Biopriming Ekstrak Bawang Merah untuk Meningkatkan Vigor dan Viabilitas Benih Kacang Hijau (Vigna radiata L.) - Freddy Alexander Simatupang; Puan Habibah; Zafitra (AgriMalS, 2026)
The success of mung bean (Vigna radiata L.) cultivation is determined by the quality of the seeds used. One effort to improve seed quality is through biopriming techniques based on natural ingredients. The purpose of this study was to evaluate the potential of shallot (Allium cepa L.) extract as a biopriming agent in increasing the viability and vigor of mung bean seeds, and to determine the optimum effective concentration. This study was conducted at the Ecophysiology Laboratory, Department of Agrotechnology, Faculty of Agriculture, University of Riau. The experimental design in this study was a completely randomized design (CRD) with one factor with six levels of shallot extract concentration, namely 0% (control), 5%, 10%, 15%, 20%, and 25% with four replications. The observation parameters consisted of germination power and germination rate, vigor index I and II, hypocotyl length, root length, fresh weight, and dry weight of the sprouts. Data analysis used ANOVA and Duncan's advanced test at the 5% level, and was supplemented with effect size analysis with eta-squared (η²). The results showed that 15% extract concentration was the optimum concentration in increasing germination rate and vigor II index. Germination rate and vigor II index decreased in direct proportion to the increase in extract concentration. The application of shallot extract had no significant effect on germination rate, hypocotyl length, root length, dry weight, and fresh weight of mung bean sprouts.